STRATEGIC DEVELOPMENT OF MAKASSAR NEW PORT THROUGH SWOT ANALYSIS, BOSTON CONSULTING GROUP AND GENERAL ELECTRIC - Andris Soma Usyor; Abdul Rahman Kadir; Nuraeni Kadir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2021)
This research aims to examine the right strategy development of Makassar New Port through the SWOT approach, Boston Consulting Group and General Electric. This research uses a quantitative and qualitative approach, the sample used is 30 directors and all levels of PT Pelindo IV (Persero). Analysis of the data used in this study is the SWOT analysis, BCG (Boston Consulting Group) and GE (General Electric). The results showed that with an established company condition with consistent profitability achievement, the strategy selection used by using the QSPM method was to strengthen its strategic position in developing the Makassar New Port and to map business potential in order to support the Makassar New Port as part of the Main Sea Corridor in Indonesia East. From the results of the BCG and General Electric matrix analysis, the position of Makassar New Port is in the position of Stars and Growing Selective. Associated with Makassar's position in the SWOT analysis, the strategy to strengthen the strategic position of Makassar New Port is most suitable for use in business development and competition.